Relationship between unintended pregnancy and the first antenatal care visit - Cahyawati, Safitri Putri; Hakimi, Mohammad; Nurdiati, Detty Siti (BKM Public Health and Community Medicine, 2021)
Purpose: The first timely antenatal care can detect complications during early pregnancy, such as hemorrhage, anemia, diabetes, and other infectious diseases. The province of Papua has the three lowest antenatal care K1 coverage areas, at 56.02%, and Jayapura city has an antenatal care K1 coverage of 51.49%. Methods: This research employed a mixed-methods approach using a sequential explanatory design. In the first stage, a quantitative approach was conducted using a cross-sectional research design. In the second stage, a qualitative approach was applied through in-depth interviews. Results: Multivariable analysis showed that unintended pregnancies were 2.8 times more likely to result in delayed first antenatal care visits compared to planned pregnancies (AOR 2.62; 95% CI: 1.23–6.25), after controlling for partner/spouse support, exposure to mass media, gestational interval, and education level. Interview findings revealed that other contributing factors to delayed first antenatal care visits included low awareness about the importance of timely care, being too busy, and a lack of knowledge regarding the benefits of antenatal care. Conclusion: The importance of family planning counseling for reproductive women is to manage and plan their pregnancies.